The History of Human Communication: How Did Humans Build Language and Become World Leaders - Morissan, Morissan (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The study of human communication history is currently very limited and even if there is, it is still limited to the discussion of the history of mass media such as newspapers, radio, and television, which began to appear at the end of the 19th century. There is no communication study that discusses how humans (Homo sapien) first, tens of thousands of years ago, communicated as humans. How did Sapiens create a language that distinguished him from animals? How did prehistoric humans use language to build group communication so that they became effective hunters and gatherers? This article aims to show how the sciences of history and biology have played a major role in building our understanding of the beginnings of human communication as a foundation for understanding communication itself. Research method used is the qualitative approach where it utilizes a review of the relevant academic publication to provide a comprehensive explanation of the raised questions. To conduct the review, an extensive and integrative search of articles published in major organizational academic research was performed. The integrative approach to systematic literature review used in this article differs from meta-analysis in that it does not utilize econometric and statistical procedures for data synthesis and analysis.The results show, based on previous studies, that Sapiens first communicated as humans when they were able to create abstract objects, which are things that simply don't exist in this world. Sapien is a leader over other animals because of this ability. Effective group communication builds on Sapien's pleasure in gossip. Ultimately, the ability to construct fiction and myth allowed Sapien to build organizations, nations, and even empires.